The Effect Of Health Education Using Video To Increase Community Knowledge And Attitude Regarding Hypertension Diseases In Terebino Village: Health Education Using Video - Tasnim, Tasnim; Ratnasari, Ratnasari; Gatra, Fandy (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Hypertension diseases in Terebino Village have the highest ranking of the 4 villages in the Ulunambo Health Center area, namely 431 cases. Meanwhile, in other villages, such as Padei Laut Village, there were only 362 cases, in Padala Village there were 329 cases, and in Kofalagadi Village there were only 282 cases. This research aims to analyze the effect of counseling on community knowledge and attitudes about hypertension in Terebino Village. Methods: The type of research used is Pre-Experimental Study using the Pretest-Posttest Designs. The population in this study was 74 families, with a proportional random sampling technique, namely 63 respondents. The analysis method uses the T-Independent test. Results: The statistical tests using the T-Independent test showed there is an influence of education through video media on people's knowledge and attitudes regarding hypertension in Terebino Village (p<0.000 of knowledge; p<0.000 of attitude). Conclusions: Health education using video media is effective in increasing public knowledge and attitudes about preventing hypertension in Terebino Village. Thus, health promotion towards increasing awareness and knowledge about hypertension is really needed for the community in Terebino Village to control hypertension.